2010
DOI: 10.1007/s10600-010-9658-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from the leaves of Synsepalum dulcificum

Abstract: 547.918Synsepalum dulcificum Daniell (Sapotaceae) is an evergreen shrub native to tropical West Africa, and the fruits, and red berries have the property of modifying sour taste into sweet taste remarkably. Interestingly, the active material of the berry is the protein, miraculin, which has no taste in itself. The sweetness intensity induced by 0.02 M citric acid after 0.4 M purified miraculin solution is held in the mouth is equivalent to that of about 0.3 M sucrose. This value is equal to the maximum sweetne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…Its phytochemical compounds were also analysed since the region of plantation might contribute to the phytochemical discrepancy. The previous studies of methanol extract of S. dulcificum leaves collected from two countries showed that the chemical compounds were different (Chen et al, 2010;Obafemi et al, 2017b). In the present study, the chemical compounds of S. dulcificum leaves was analysed by gas chromatographymass spectrometry (GC-MS) because this technique is highly sensitive, fast and no standards are needed since the identification of the chemical compounds was carried out by comparing the mass spectra with the libraries (Hübschmann, 2015).…”
Section: Determination Of Minimum Inhibitory Concentrations (Mic)mentioning
confidence: 99%
See 1 more Smart Citation
“…Its phytochemical compounds were also analysed since the region of plantation might contribute to the phytochemical discrepancy. The previous studies of methanol extract of S. dulcificum leaves collected from two countries showed that the chemical compounds were different (Chen et al, 2010;Obafemi et al, 2017b). In the present study, the chemical compounds of S. dulcificum leaves was analysed by gas chromatographymass spectrometry (GC-MS) because this technique is highly sensitive, fast and no standards are needed since the identification of the chemical compounds was carried out by comparing the mass spectra with the libraries (Hübschmann, 2015).…”
Section: Determination Of Minimum Inhibitory Concentrations (Mic)mentioning
confidence: 99%
“…Although steroid was identified in small percentage, this compound was not identified in methanol extract of S. dulcificum leaves obtained in Nigeria (Obafemi et al, 2017b). On the other hand, methanol extract of S. dulcificum leaves collected in Taiwan showed the presence of steroids such as β-sitosterol and stigmasterol (Chen et al, 2010). This finding showed that the cultivation area might influence the chemical compounds of the S. dulcificum.…”
mentioning
confidence: 96%
“…The flowers are white with about 2-2.5 cm long fruits and gives red colour when ripe; each fruit contains one seed [6]. The active component present in the berry is the glycoprotein called miraculin which has no taste in itself [7]. When the fruit pulp is licked, it miraculously turns sour foods such as limes, lemons, vinegar etc.…”
Section: Introductionmentioning
confidence: 99%
“…This explains why the berry has been called "miracle fruit or mysterious fruit". In the course of screening for chemically novel agents from plants, S. dulcificum was chosen for further phytochemical investigation [2][3][4][5]. In this study, the MeOH extract of its stems was subjected to chromatographic separation to afford six pure compounds, including propane-1,2,3-triol (1), 2,5-dimethoxyphenol (2), 3,4,5-trimethoxybenzoic acid (3), nicotinic acid (4) [6], E-sitosterol (5), and stigmasterol (6) [7].…”
mentioning
confidence: 99%
“…In this study, the MeOH extract of its stems was subjected to chromatographic separation to afford six pure compounds, including propane-1,2,3-triol (1), 2,5-dimethoxyphenol (2), 3,4,5-trimethoxybenzoic acid (3), nicotinic acid (4) [6], E-sitosterol (5), and stigmasterol (6) [7]. Among them, 2 was isolated from natural sources for the first time though they had been synthesized previously [8], and 1-4 were obtained for the first time from this plant [2][3][4][5]. In this paper, we report the isolation and structure elucidation of 2.…”
mentioning
confidence: 99%